Growth and Management Effect of Larix Principis-rupprechtii Plantation - Wang Zhengan; Yu Zhijia; Wang Zhenzhong; Wu Miao; She Ping; Ma Jie; Jia Baoguang (Shuitu baochi tongbao)
[Objective] The effect of growth and management of a Larix principis-rupprechtii plantation was analyzed in order to provide a reference for the scientific and rational management of L. principis-rupprechtii plantations by giving full attention to ecological functions and cost-effectiveness. [Methods] The methods used in this study included consulting archives, conducting interviews, and field investigations regarding the input costs and growth of stands of the main L. principis-rupprechtii under traditional forest management and under near-natural forest management in Yuanzhou District, Guyuan City, Ningxia Hui Autonomous Region located in the upper reaches of the Jinghe River basin. Measured parameters included input costs, average diameter at breast height, average tree height, stock volume per hectare, and aboveground biomass of per hectare. The fuzzy mathematics subordination function value method was used to quantitatively compare and evaluate the growth of trees. [Results] The growth of trees under different forest management models was significantly dissimilar. The average height, diameter at breast height, stock volume per hectare, and aboveground biomass per hectare at Huangjiagou and Diediegou under near-natural forest management were greater than under traditional forest management. The comprehensive evaluation of the growth effect of the many plantations of L. principis-rupprechtii under different management models in Yuanzhou District of Guyuan City was extremely obvious (p<0.05). The stand growth effect followed the order (ranging from strong to weak) of Huangjiagou (0.995 8)>Diediegou (0.628 8)>Qingshixia(0.224 6)>Hongzhuangliang (0.222 7)>Madong Mountain (0.159 8)>Chenger Mountain (0.048 6)>Longdegou (0.000 0). [Conclusion] Tree growth under the traditional forest management model was poor. Therefore, implementation of multi-functional and near-natural target tree management measures is conducive to cultivating large diameter timber to accelerate the growth of forests.